2011
DOI: 10.7124/bc.000119
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of serum albumins with cluster rhenium compounds of cis- and trans-configuration

Abstract: Aim. To investigate differences in the interactions of binuclear cluster rhenium(III) compounds of cis(I)and trans(II)-configuration with bovine serum albumin (BSA) and human serum albumin (HSA). Methods. Electronic spectroscopy, tryptophan fluorescence and circular dichroism spectroscopy. Results. It was shown that in the process of interaction of I and II with proteins different complexes were formed where the quadruple bond Re–Re remained. Conclusions. It is proposed that the trans-isomer interacts with mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…As is shown in Figure 9, the fluorescence intensity decreased regularly with the titration of SPION-DNM, indicating that the drug delivery alters the spatial structure of HSA and therefore increases the exposure of Trp-212 to the medium indirectly, which leads to a less hydrophobic environment of the fluorescence chromophore placed. 28,29 The newly appeared shoulder peak located at 310 nm could be attributed to the new state of SPION-DNM bound HSA, 30 which also confirms the tight binding between the nanospheres and protein.…”
Section: Probing the Interaction Of Spion-dnm With Hsasupporting
confidence: 51%
See 1 more Smart Citation
“…As is shown in Figure 9, the fluorescence intensity decreased regularly with the titration of SPION-DNM, indicating that the drug delivery alters the spatial structure of HSA and therefore increases the exposure of Trp-212 to the medium indirectly, which leads to a less hydrophobic environment of the fluorescence chromophore placed. 28,29 The newly appeared shoulder peak located at 310 nm could be attributed to the new state of SPION-DNM bound HSA, 30 which also confirms the tight binding between the nanospheres and protein.…”
Section: Probing the Interaction Of Spion-dnm With Hsasupporting
confidence: 51%
“…As has been thoroughly emphasized, the fluorescence of Trp and Tyr residues is highly sensitive to the polarity of its environment, which usually presents a red shift in a more polar surrounding. [27][28][29][30] Thus, the emission shifts of the amino acid residues could be employed to examine the conformational changes of protein. To further probe the binding mechanism of the SPION-DNM nanospheres and HSA, synchronous fluorescence spectroscopy experiment was carried out to investigate the conformational changes of protein.…”
Section: Probing the Interaction Of Spion-dnm With Hsamentioning
confidence: 99%
“…We investigated differences in the interactions between binuclear cluster rhenium(III) compounds of cis-and trans-configuration with native bovine serum albumin (BSA) and human serum albumin (HSA) by methods of electronic absorbtion spectroscopy, tryptophan fluorescence and circular dichroism spectroscopy [94]. It was shown that in the process of interaction of both compounds with proteins the formation of the different complexes took place via His moieties with preservation of quadruple Re-Re bond.…”
Section: Fig 7 Level Of Mda In Plasma Of Control (C) Rats and Tumormentioning
confidence: 99%
“…Fluorescence was measured in phosphate buffer pH 7.4 using spectrofluorimeter Shimadzu RF-5301 PC (Japan), slit width EX: 10.0 nm and EM: 10.0 nm, excitation wavelength 290 nm [8]. The effect of the compound i in a molar ratio of 1(SOD):10(i) was studied immediately after mixing.…”
Section: Methodsmentioning
confidence: 99%